Community Driven Development Model Pada Program Gerbang Cahayaku di Desa Tanjungsari Kecamatan Karangpawitan Kabupaten Garut - Kurnia, Dhita Amelia; Miradhia, Darto (Majalah Ilmiah UNIKOM, 2024)
The development paradigm shift has now developed towards human-based development by focusing on community participation. This is based on the belief that the community knows best what they need. This study aims to describe the application of the Community Driven Development model in the Gerbang Cahayaku programme implemented in Tanjungsari Village, Karangpawitan District, Garut Regency. The analysis was conducted using three important aspects that are specific characteristics in this model, namely decentralisation, democratisation, and collective action. The research method used is descriptive qualitative to produce a description of the factual issues raised systematically. The results showed that in general the implementation of Gerbang Cahayaku carried out in Tanjungsari Village has fulfilled the three main aspects that characterise the Community Driven Development model. Decentralisation relates to the transfer of authority from Disperkim to Community Self-Help Group to manage development activities, from planning, implementation, to supervision. Democratisation relates to the implementation of local governance and participatory decision-making process by involving the community. Finally, collective action relates to community mobilisation that occurs inclusively to be directly involved in all stages of development activities. Key Words: The development of villages, community driven development, decentralization, democratization, collective action